2013
DOI: 10.3989/gya.119712
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma radiation on the lipid profiles of soybean, peanut and sesame seed oils

Abstract: RESUMENEfecto de la radiación gamma sobre el perfil lipídico de los aceites de semillas de soja, cacahuete y sésamo Semillas de soja, cacahuete y de sésamo se expusieron a diferentes dosis de radiación gamma (0,0, 0,5, 1,0, 2,0, 3,0, 5,0 y 7,5 kGy). Se determinaron los perfiles de ácidos grasos y el insaponificable de los aceites mediante cromatografía de gases y espectrometría de masas. Los resultados demostraron que las relaciones de ácidos insaturados a ácidos grasos totales saturados (TU/TS) e hidrocarburo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 32 publications
2
10
1
Order By: Relevance
“…The present finding agrees with those obtained by Afify et al [7] on peanut seed treated with dose up to 7.5 kGy. Similar results were reported by Olotu et al [2] for fatty acid profile of African oil bean seeds treated with 10 kGy of gammairradiation.…”
Section: Effects Of Gamma-irradiation On Fatty Acid Of Peanut Seed Oilsupporting
confidence: 83%
See 4 more Smart Citations
“…The present finding agrees with those obtained by Afify et al [7] on peanut seed treated with dose up to 7.5 kGy. Similar results were reported by Olotu et al [2] for fatty acid profile of African oil bean seeds treated with 10 kGy of gammairradiation.…”
Section: Effects Of Gamma-irradiation On Fatty Acid Of Peanut Seed Oilsupporting
confidence: 83%
“…The present findings agree with previous studies, where it was found that gamma-irradiation had some effects on the physical and chemical composition of soybeans [29]. In contrast to our results, the fatty acid linoleic C18:2 is considered to be the most affected one by gamma-radiation which was decreased by over 2% followed by oleic C18:1 when irradiated at 7.5 kGy [7]. Finally Al-Bachir, [11] indicated that, SFA and USFA of …”
Section: Data Incontrasting
confidence: 57%
See 3 more Smart Citations